(3QSGdI GdfaY GdYGe aj GdYed HGdQHY GdJGes - (3Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, CHh GdMSf YdGA GdOjf, GdeYQha HGHf GdTGWQ,J (B777 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3aEfi CeYfJ GdfXQ ai GdBdGJ GdadcjI GdehUdg Edi eYQag GdChbGJ GdTQYjg s
(3BNQgG (B:s
(3abO PcQJ Pdc ai QSGdI CNQi SejJgG HGdeRjO (B"(3GdeQi ai GdYed HGdLjH HZjQ eQi(B" s
(3Vef eLehY , JQJjHgG (B: (3ef U (B34 - (3U(B110s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B126 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B138) s
Keywords: (3Gdadcs